3256 Effectiveness of Shared Decision-Making for Diabetes Prevention: 12-month Results from the Prediabetes Informed Decision and Education (PRIDE) Randomized Trial. (27th March 2019) - Moin, Tannaz; Kenrik Duru, O.; Turk, Norman; Chon, Janet S.; Frosch, Dominick L.; Martin, Jacqueline; Jeffers, Kia Skrine; Castellon-Lopez, Yelba; Tseng, Chi-Hong; Norris, Keith; Mangione, Carol M.
Abstract : OBJECTIVES/SPECIFIC AIMS: Intensive lifestyle change (e.g., the Diabetes Prevention Program) and metformin reduce type 2 diabetes risk among patients with prediabetes. However, real-world uptake remains low. Shared decision-making (SDM) may increase awareness and help patients select and follow through with informed options for diabetes prevention that are aligned with their preferences.The objective was to test the effectiveness of a prediabetes SDM intervention. METHODS/STUDY POPULATION: This was a cluster-randomized controlled trial in 20 primary care clinics within a large regional health system. Participants were overweight/obese adults with prediabetes (BMI>24 kg/m2 and HbA1c 5.7-6.4%) were enrolled from 10 SDM intervention clinics. Propensity score matching was used to identify control patients from 10 usual care clinics.Intervention clinic patients were invited to participate in a face-to-face SDM visit with a pharmacist who used a decision aid (DA) to describe prediabetes and four possible options for diabetes prevention; DPP, DPP +/− metformin, metformin only, or usual care. RESULTS/ANTICIPATED RESULTS: Uptake of DPP and/or metformin was higher among SDM participants (n=351) than controls receiving usual care (n = 1, 028; 38% vs. 2%, p<.001). At 12-months follow-up, adjusted weight loss (lbs.) was greater among SDM participants than controls (−5.3 vs. −0.2, p < .001). DISCUSSION/SIGNIFICANCE OF IMPACT: A prediabetes SDM intervention led by pharmacists increased patient engagement in evidence-based options for diabetes prevention and was associated with significantly greater uptake of DPP and/or metformin at 4-months and weight loss at 12-months. Prediabetes SDM may be a promising approach to enhance prevention efforts among patients at increased risk.